Service Delivery of Non-Governmental Organizations in Somaliland: The Role of Strategy Implementation Drivers - Nkanata, Mwongera Bornface; Mungara, Maria (Journal Integration of Social Studies and Business Development, 2024)
This paper examines the relationship between strategy implementation and service delivery among Non-Governmental Organizations (NGOs) in Somaliland. This study is motivated by the increasing need for sustainable NGOs capable of effectively fulfilling their mandates and the lack of empirical evidence on strategy implementation in Somaliland. The research focuses on key drivers of strategy implementation: financial resources, organizational leadership, organizational structure, and organizational culture. The theoretical framework of this paper is anchored in the resource-based view theory and institutional theory. Utilizing a descriptive research design, the study surveyed 86 respondents from Save the Children, a leading NGO in Somaliland. Using a sampling formula, these respondents were selected from a target population of 110 employees. Data collection was conducted using a structured questionnaire. Descriptive and inferential analyses were performed using SPSS version 27. The findings indicate that organizational structure significantly influences service delivery among NGOs. Additionally, organizational leadership plays a crucial role in determining the effectiveness of service delivery. Financial resources also have a substantial impact on influencing service delivery. Lastly, organizational culture is identified as a critical driver of strategy implementation, significantly affecting service delivery. The study concludes that strategy implementation is a vital determinant of how well NGOs deliver their mandates, with its success heavily reliant on the supporting drivers of implementation.